The Great Recession and racial inequality: Evidence from measures of economic well-being - Thomas Masterson; Ajit Zacharias; Fernando Rios-Avila; Edward N. Wolff (Levy Economics Institute of Bard College, 2017)
The Great Recession had a tremendous impact on low-income Americans, in particular black and Latino Americans. The losses in terms of employment and earnings are matched only by the losses in terms of real wealth. In many ways, however, these losses are merely a continuation of trends that have been unfolding for more than two decades. We examine the changes in overall economic well-being and inequality as well as changes in racial economic inequality over the Great Recession, using the period from 1989 to 2007 for historical context. We find that while racial inequality increased from 1989 to 2010, during the Great Recession racial inequality in terms of the Levy Institute Measure of Economic Well-Being (LIMEW) decreased. We find that changes in base income, taxes, and income from nonhome wealth during the Great Recession produced declines in overall inequality, while only taxes reduced between-group racial inequality
Keywords: D31; D63; I31; J15; 330; LIMEW; United States; Great Recession; Race; Distribution of Wealth; Distribution of Income